Evaluation of Inclusive Learning Programs for Students with Special Needs (Autism) - Masfui, Moh; Badrudjaman, Aip; Mahdiyah, Mahdiyah (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
Inclusive education from primary to higher education has been implemented in many countries around the world, even before the issuance of the UN Convention in 2008. In Indonesia, the UN Convention immediately received a response from the Government and the public through the DPR, in the form of ratification into Law of the Republic of Indonesia no 19 of 2011. The purpose of this study is to elaborate on the form of evaluation of inclusive learning programs for students with special needs (autism). The research method used is the qualitative research method. The results of the study show that good evaluation activities are activities that are able to provide feedback as a form of improvement for a program from all aspects. The CIPP model is considered suitable for evaluation studies on the implementation of inclusion studies for autistic students. Program evaluation has a measure of success called a criterion. With the reference criteria, various components in the program that have been achieved can be considered. The criteria are said to be successful and successful if they meet the established success criteria.